The Effect of Work-Life Balance and Job Satisfaction on Organizational Citizenship Behavior at PT IGP Bantul International - Mubarokah, Nazula; Susana, Susana; Astuti, Isna Puji; Kurniawati, Aprilia (DAS Institute, 2025)
Seeing the importance of work-life balance and job satisfaction for OCB in a company. This study aims to find out whether work-life balance and job satisfaction affect organizational citizenship behavior or not. The respondents in this study were 30 respondents who were employees of PT IGP Internasional Bantul. The results in this study show that work-life balance and job satisfaction have a simultaneous effect on Organizational Citizenship Behavior (OCB) at PT IGP Internasional Bantul.